Exploration of the Factors Associated with Psychiatric Nurses Skills with Patient Care: A Cross-Sectional Survey (Central Asian Journal of Medical Sciences, 2021)
Objectives: Numerous studies revealed that improved nursing skills are associated with the experience of the nurses, social skills, self-education, autonomy, anxiety. In the present study, we have examined whether nursing skills are related to occupational stress. Methods: An institution based cross sectional study was conducted from June 20 to December 25, 2020. A total of one hundred and forty-four psychiatric nurses completed a questionnaire assessing the aforementioned variables. Descriptive statistics and independent t-test were used to determine the characteristics of the participants and examine the difference among different variables. Results: During the one-month data collection period, 144 psychiatric nurses were included in the analysis. Mean age of the participants were 39.3 ± 9.4. The majority (127 (88.2%)) of them were female. Of 144 respondents, 83 (57.6%) had a bachelor’s degree and 6 (6%) had a higher degree certification. Comparison by courses, those who studied psychiatry more than 3 months reported greater knowledge of psychiatric services. Certification was also associated with greater perceived value. Education level was not associated with greater knowledge of or perceived value in evidence -based practices. Conclusion: Nursing specialty certification was associated with nurses’ individual psychosocial beliefs. Supporting nurses in obtaining specialty certification could assist with the adoption of evidence-based practices as a means to improve quality of care.